BENTUK TARI MANOE PUCOK PADA MASYARAKAT BLANGPIDIE ACEH BARAT DAYA - Novinta Sari (Universitas Negeri Medan, 2016)
Based on research that has been done, the history of dance ManoePucokderived from malelang-madion story taken from the story of dance Pho.Where they were executed as a result of slander prime minister, where thegrief of a mother loses her daughter forever. Based on this story, danceManoePucok no longer tells of the sadness of a mother on her daughter diedas a result of execution. But this ManoePucok dance tell the sadness of amother, who lost her daughter to remove the bachelor married to happiness.This form of dance is twofold, form the internal structure and externalstructure forms. We can see the internal form of grief a mother take off herdaughter into a new life, through internal forms of dance ManoePucok, themother expressed her sorrow to remove the bachelor. External shape seenfrom the motion that the entrance motion, shalawat motion, Trontajakmanoemotion, taking water motion, flush head motion, TrontajakManoe motion, themotion of hair shampoo and body motion flush. There are six forms the floorpattern, the pattern of two lines up, a triangle pattern, the pattern of v, thepattern of the two row, and a half-circle pattern. Accompaniment, fashion,and makeup, which have meaning ManoePucok dance performances.ManoePucok dance is performed before the consent granted do